The Effects of Ideal Production Stabilization: A Welfare Analysis under Rational Behavior - Wright, Brian D. (Journal of Political Economy, 1979)
This paper focuses on the welfare effects of output instability and its elimination. Assuming Muthian rationality, risk neutrality, and lagged production response, I show how output instability affects the long-run production incentive. The gains and losses from the elimination of output disturbances ("ideal stabilization") are evaluated, and simple general conditions are derived which determine whether producers or consumers can expect to gain or lose from such stabilization. The distribution of the gains is generally more evenhanded than indicated in previous expectational models of price stabilization, which can be interpreted as special cases of this model.